Study on Mechanism of Extraction of Palladium(II) with 2-Ethylhexyl Benzimidazole Sulfide - Feng, Shaoping; Li, Zijing; Huang, Zhangjie; Huang, Zhaolong; Liu, Wei (Asian Journal of Chemistry, 2014)
The mechanism of extraction of Pd(II) with 2-ethylhexyl benzimidazole sulfide was studied. Experimental results show that the distribution coefficient of Pd(II) was not affected by the H+ concentration, but decreased dramatically with the increase of Cl- concentration in hydrochloric acid. PdCl2·2-ethylhexyl benzimidazole sulfide complex has been identified with the infrared spectrum, UV-visible spectrum and slope. The possible mechanism of palladium extraction with 2-ethylhexyl benzimidazole sulfide determined to be neutral coordination. It reveals that 2-ethylhexyl benzimidazole sulfide coordinates with Pd(II) via the benzimidazole N atom and the molar ratio of 2-ethylhexyl benzimidazole sulfide to Pd(II) was 2:1.